China's quest for political legitimacy : the new equity-enhancing politics - Guo, Baogang, 1960- (Challenges facing Chinese political development., 2010)
This book is a study of China's quest for political legitimacy within the context of traditional Chinese political culture. Through examinations of the new governing philosophy, the new generation of political elite, and a number of public policies, the books reveals some surprising new trends in Chinese political development, such as the endorsement of deliberative democracy, new waves of citizen activism, and a new era of social legislation.